2007
DOI: 10.1109/iembs.2007.4352642
|View full text |Cite
|
Sign up to set email alerts
|

NIR Light Penetration Depth in the Rat Peripheral Nerve and Brain Cortex

Abstract: Near infrared (NIR) light energy has been used in medical applications both for diagnostic and treatment purposes. A priory knowledge of optical tissue properties is necessary in these applications; not only of human but also in animals for testing of devices. However, published data on the optical properties of neural tissue in rodents are rare. The aim of this study was to measure the penetration depth of light into the rat peripheral nerve and brain cortex at NIR wavelengths. Penetration depth was calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…42,80 In gray matter, red and near-infrared light penetration is governed by Beer -Lambert law, with the optical power decaying up to 80% at 1 mm from the surface. 81 However, at this depth in solid organs, the actual power density of near-infrared light has been estimated to be up to three times higher than the power at the incident surface due to backscattering and constructive interference. 82 As the light travels into the tissue, its intensity decreases due to absorption and scattering.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…42,80 In gray matter, red and near-infrared light penetration is governed by Beer -Lambert law, with the optical power decaying up to 80% at 1 mm from the surface. 81 However, at this depth in solid organs, the actual power density of near-infrared light has been estimated to be up to three times higher than the power at the incident surface due to backscattering and constructive interference. 82 As the light travels into the tissue, its intensity decreases due to absorption and scattering.…”
mentioning
confidence: 98%
“…The maximal penetration of light in the gray and white matter of the brain occurs at wavelengths in the near-infrared spectrum. 81 It has been shown that within the visible and near-infrared spectral range, white matter in both the central and peripheral nervous systems reflects most of the incident power and shows a low level of absorption and a short penetration depth. 83 In contrast, the transmittance of the gray matter is approximately twice as high as that of the white matter (Figure 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The penetration depth of a Smart FLAMES is variable and because the amount of attenuation of near infrared (NIR) light [14], [15] has a direct effect on the amount of absorbed power from an illumination source; the Smart FLAMES device must be able to work across a large range of supply conditions. The photovoltaic response is simulated using a current source in parallel with a diode device.…”
Section: Simulations and Resultsmentioning
confidence: 99%
“…While high responsivities have been reported with standard CMOS photodiodes (0.37A/W) [16], a conservative assumption of 0.05A/W will be used when calculating the minimum required optical power. The optical penetration of NIR light in the CNS can be estimated as 10% at a distance of 1mm [14], [17], a depth comparable to similar stimulation electrodes. A worst-case assumption would be for the highest stimulation current, 1mA.…”
Section: Usage Parametersmentioning
confidence: 96%